2015
DOI: 10.1038/ki.2014.286
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Krüppel-like factor 2 expression may aggravate the endothelial injury of diabetic nephropathy

Abstract: Kruppel-like Factor 2 (KLF2), a shear-stress inducible transcription factor, has endoprotective effects. In streptozotocin-induced diabetic rats, we found that glomerular Klf2 expression was reduced in comparison to non-diabetic rats. However, normalization of hyperglycemia by insulin treatment increased Klf2 expression to a level higher than that of non-diabetic rats. Consistent with this, we found that Klf2 expression was suppressed by high glucose but increased by insulin in cultured endothelial cells. To d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 56 publications
2
60
1
Order By: Relevance
“…30 We also recently showed that eNOS expression was reduced in the diabetic Klf2 heterozygous KO mice as compared to diabetic WT mice. 18 Similarly, we observed herein that mRNA levels of eNOS were significantly decreased in the glomeruli of KO-UNX as compared to all other groups ( Figure 4A). Reduction of eNOS specifically in the KO-UNX glomeruli was further confirmed at the protein level by immunostaining (Figure 4, B and C) and by Western blot analyses (Figure 4, DeF).…”
Section: Reduced Klf2 Expression Results In Increased Glomerular Endosupporting
confidence: 82%
See 4 more Smart Citations
“…30 We also recently showed that eNOS expression was reduced in the diabetic Klf2 heterozygous KO mice as compared to diabetic WT mice. 18 Similarly, we observed herein that mRNA levels of eNOS were significantly decreased in the glomeruli of KO-UNX as compared to all other groups ( Figure 4A). Reduction of eNOS specifically in the KO-UNX glomeruli was further confirmed at the protein level by immunostaining (Figure 4, B and C) and by Western blot analyses (Figure 4, DeF).…”
Section: Reduced Klf2 Expression Results In Increased Glomerular Endosupporting
confidence: 82%
“…Our previous study showed a 50% reduction of Klf2 mRNA expression in isolated glomerular endothelial cells from KO kidneys as compared to those from WT kidneys. 18 In addition, at baseline, KO mice did not exhibit albuminuria, glomerular injury, or tubulointerstitial disease when examined at 6 and 12 months of age (data not shown).…”
Section: Generation Of Endothelial Cellespecific Klf2 Heterozygous Knmentioning
confidence: 87%
See 3 more Smart Citations